Answer

Verified

403.2k+ views

**Hint:**In this type of problem first you must make sure that there is no present square root and cube root of any variables. If available we try to remove it by applying the algebraic formula.

**Complete step-by-step solution:**Here in the question the given equations are

$x + \sqrt {xy} + y = 65$

$x + y = 65 - \sqrt {xy} $……......… let it be equation (1).

${x^2} + xy + {y^2} = 2275$….....… let it be equation (2).

Using ${\left( {a + b} \right)^2} = {a^2} + {b^2} + 2ab$

Here, on adding xy both side in equation(2) We can write it as:

${\left( {x + y} \right)^2} - xy = 2275$….. Let it be equation (3).

Substituting equation (1) in equation (2), we have

$ \Rightarrow {\left( {65 - \sqrt {xy} } \right)^2} - xy = 2275 \\

\Rightarrow 4225 + xy - 130\sqrt {xy} - xy = 2275 \\

\Rightarrow - 130\sqrt {xy} = - 1950 \\

\Rightarrow \sqrt {xy} = 15 \\

\Rightarrow xy = 225 \\

\Rightarrow y = \dfrac{{225}}{x} \\ $

$\therefore y = \dfrac{{225}}{x}$

Now put the value of y in equation (2) we get,

$\Rightarrow {x^2} + {\left( {\dfrac{{225}}{x}} \right)^2} + x \cdot \dfrac{{225}}{x} = 2275 \\

\Rightarrow {x^2} + \dfrac{{50652}}{{{x^2}}} = 2050 \\

\Rightarrow {x^4} - 2050{x^2} + 50652 = 0 \\

\Rightarrow {x^4} - 25{x^2} - 2025{x^2} + 50625 = 0 \\

\Rightarrow {x^2}\left( {{x^2} - 25} \right) - 2025\left( {{x^2} - 25} \right) = 0 \\

\Rightarrow \left( {{x^2} - 2025} \right)\left( {{x^2} - 25} \right) = 0 \\

\Rightarrow {x^2} = 25,2025 \\

\therefore x = \pm 5, \pm 45 $

Negative values of x are not satisfied by (1)

So, $x = 5, 45$

Now put the value of x in $y = \dfrac{{225}}{x}$ to find the value of y.

When $x=5, \Rightarrow y = \dfrac{{225}}{5} = 45$

When$ x=45, \Rightarrow y = \dfrac{{225}}{{45}} = 5$

Therefore, the values of x are 5, 45 and corresponding values of y are $45, 5.$

**Hence options A and D are the correct answer.**

**Note:**Whenever you come to this type of problem when we solve equations, we should make sure that equations don’t contain the square root & cube root of any variable. If it is then converting it to a simple form for reducing the complexity of the calculations and after that solve the equations.

Recently Updated Pages

The base of a right prism is a pentagon whose sides class 10 maths CBSE

A die is thrown Find the probability that the number class 10 maths CBSE

A mans age is six times the age of his son In six years class 10 maths CBSE

A started a business with Rs 21000 and is joined afterwards class 10 maths CBSE

Aasifbhai bought a refrigerator at Rs 10000 After some class 10 maths CBSE

Give a brief history of the mathematician Pythagoras class 10 maths CBSE

Trending doubts

Difference Between Plant Cell and Animal Cell

Give 10 examples for herbs , shrubs , climbers , creepers

Name 10 Living and Non living things class 9 biology CBSE

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

Change the following sentences into negative and interrogative class 10 english CBSE

Write a letter to the principal requesting him to grant class 10 english CBSE

Fill the blanks with proper collective nouns 1 A of class 10 english CBSE

Write the 6 fundamental rights of India and explain in detail